PENGARUH PENGGUNAAN MOBILE BANKING, GAYA HIDUP, DAN PENDAPATAN TERHADAP PERILAKU KONSUMTIF MASYARAKAT PADA GENERASI Z DI KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Ferdi Anggriawan; Ahlan Nur; Fifi Fadila (Bajang Institute, 2026)
This study aims to determine the influence of mobile banking usage, lifestyle and income on the consumer behavior of Generation Z in Timang Gajah District. The research question is whether mobile banking usage, lifestyle, and income influence the consumer behavior of Generation Z in Timang Gajah District. The researcher distributed questionnaires to 248 respondents.This study uses quantitative methods. Data analysis in this study uses multiple linear regression methods. The results of the study indicate that there is no positive influence between the use of mobile banking (X1) on people's consumptive behavior (Y) as evidenced by the t-test significance value of 0.533 which is greater than α = 0.05. Lifestyle (X2) has a positive influence on people's consumptive behavior (Y) as evidenced by the t-test significance value of 0.000 which is smaller than α = 0.05. Likewise, income (X3) has a positive influence on people's consumptive behavior (Y) as evidenced by the t-test significance value of 0.000 which is smaller than α = 0.05. The results of the Determination Coefficient (R²) test show a value of 0.505. This indicates that the use of mobile baking, lifestyle, and income together have a positive and significant influence on consumer behavior by 50.5%, while the remaining 49.5% is influenced by other variables not explained in this study. Therefore, it is necessary to have the principle of appropriate technology and limit individual shopping activities, such as buying products according to needs, setting aside money for savings, and recording daily transactions to prevent consumptive behavior.